USING THE CONCEPT OF KNOWLEDGE MAPS FOR THE AMELIOURATION OF KNOWLEDGE MANAGEMENT SYSTEMS - Zajemski , Zbysław; Skibiński, Andrzej; Biniek - Poskart , Anna; Zajemska, Monika (Management and Administration Journal, 2024)
The appropriate localisation and mapping of knowledge resources in an enterprise is a necessary element for efficient knowledge management. This requires appropriate motivation on the part of employees and a number of actions on the part of managers. Looking to address this very issue, what follows presents an analysis of the process of mapping and locating knowledge resources in a selected company: one of the branches of an international company belonging to the automotive industry, located in Poland, was selected as the research object. The results of the research were used to develop proposals for solutions to improve the knowledge management system. Therefore, the aim of this publication is to diagnose the functioning of the knowledge transfer system on the example of the selected enterprise, based on an initial proprietary pilot study.